The Manners of Reading the Qur'an from the Perspective of the Book of At-Tibyan: A Study on Participants in Talaqqi Classes - Nur Madiah Harahap; Muzakkir Muzakkir (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to analyze the application of the etiquette of reading the Qur'an based on the Book At-Tibyan fi Adabi Hamalatil Qur'an in talaqqi class participants. A qualitative approach was used with a field study design, involving 15 participants selected purposively. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed thematically and validated through technical triangulation. The results show that technical-verbal etiquette, such as reading and listening in groups, raising the voice for correction, maintaining tajweed, and responding to greetings, have been consistently applied by all participants. In contrast, spiritual-social etiquette, including maintaining the quietness of the assembly, waiting for teacher corrections, responding to the call to prayer, and performing tilawah prostration, have not been consistently applied. These findings reveal a gap between mastery of technical aspects and appreciation of spiritual aspects in the application of etiquette of reading the Qur'an, which indicates that the talaqqi method is effective in improving reading competence but has not fully formed a holistic attitude of reverence towards the Qur'an. This study emphasizes the need for explicit and gradual integration of spiritual etiquette learning into the talaqqi curriculum to balance the technical and spiritual achievements of participants